Clinician and client perspectives regarding transgender health: a North Queensland focus. Issue 4 (2nd October 2019) - Heng, Audrey; Heal, Clare; Banks, Jennifer; Preston, Robyn
Abstract: Background: Healthcare encounters are important in ensuring safe access to medical or surgical care for transgender people. Previous literature suggests many transgender people have had negative encounters with healthcare professionals. In Australia, there is limited research about this population and their healthcare, and less from regional locations. Aims: This study primarily aimed to explore both transgender client and clinician perspectives and experiences of healthcare interactions. A secondary aim was to investigate increased presentations to sexual health clinics in North Queensland by people wishing to transition. Methods: Semi-structured, in-depth interviews were used to gather data from 23 participants. Interview transcripts were inductively analyzed and themes developed. Results: Four themes emerged relating to healthcare encounters and the regional setting of North Queensland. These showed that support from family and peers is important for transgender mental health and wellbeing, and that person-centered clinicians who acknowledge a holistic approach to transgender care also form part of the support network for transgender individuals particularly in the regional setting. The internet was found to play a significant role in this study's findings. Discussion: A collaborative holistic approach to transgender healthcare should be taken by client and clinician to best support the transgender individual during transition. The establishment of Australian guidelines and online peer support groups would facilitate this approach, particularly in rural or regional areas where specialist services are limited.